2022
DOI: 10.1186/s13054-022-04000-5
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of indirect calorimetry in critically ill patients: pros and cons

Abstract: To review the pros and cons of indirect calorimetry (IC) to estimate resting energy expenditure (REE) and define individual nutritional energy targets among critically ill patients. We evaluate pros, (relative) cons and when adjustments of REE are needed (Fig. 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Regarding obesity, the guidelines suggest that the goal of enteral nutrition should not exceed 65%–70% of the target REE IC [ 48 ]. Personalized nutritional adjustments may impact PICU length of stay, readmission rates, quality of life [ 49 ], and long-term rehabilitation success [ 50 ]. Scientific societies recommend measuring REE by IC in malnourished children and/or suspected altered metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding obesity, the guidelines suggest that the goal of enteral nutrition should not exceed 65%–70% of the target REE IC [ 48 ]. Personalized nutritional adjustments may impact PICU length of stay, readmission rates, quality of life [ 49 ], and long-term rehabilitation success [ 50 ]. Scientific societies recommend measuring REE by IC in malnourished children and/or suspected altered metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…We measured REE on ICU Day 3 or 4 since it has been previously shown that non-inhibitable endogenous energy is produced in the acute phase of critical illness due to a catabolic state [ 50 ]. Since the non-measurable, adapted to acute illness endogenous effect dissipates by Day 4 [ 54 ], it is recommended to commence early enteral nutrition within 24 h of admission [ 55 ], and to increase it in a stepwise fashion until the goal for delivery is achieved using a feeding protocol [ 47 ], to avoid overfeeding and mitochondrial exhaustion by targeting REE IC during the acute stress period [ 49 , 56 ]. Adult guidelines also recommend that hypocaloric nutrition (not exceeding 70% of REE IC ) should be administered in the early phase of acute illness and that isocaloric nutrition should be progressively implemented after the early phase of acute illness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses show improved survival among ICU patients when nutrition therapy is guided by indirect calorimetry. [20]…”
Section: Optimal Energy Targets In Critical Illnessmentioning
confidence: 99%
“…The absence of benefit of early full feeding has also been attributed to the absence of indirect calorimetry to guide the energy target [ 43 ]. In acute illness, indirect calorimetry is the gold standard to measure energy expenditure, which is derived from measurement of VO2 and VCO2, and the obtained value has been proposed as energy target after the first days in ICU [ 44 ]. In most recent large feeding RCTs, indirect calorimetry was not routinely used, reflecting daily practice in most centers [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most recent large feeding RCTs, indirect calorimetry was not routinely used, reflecting daily practice in most centers [ 11 15 ]. Instead, the energy target was determined by predictive equations that only provide an estimation of energy expenditure that may considerably deviate from the measured energy expenditure [ 11 15 , 44 ]. However, there is no solid evidence that the feeding target should equal energy expenditure at all times, since the largest RCTs comparing indirect calorimetry-based feeding versus predictive equation-based feeding in adult critically ill patients did not show clear benefit [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%